A transgeneridade infantil sob a ótica de professores de ensino fundamental - Silva, Francisca Vilena da (2019)
Introduction: The school context is considered a decisive part of the construction and development of the child, depending on the characteristics, beliefs, conceptions, and this can become either an exciting or exhausting or excluding environment. Objective: This study aimed at analyzing the transgender children 's perspective and identifying, in the teachers' conception, the possibilities / limits of working with transgender children in the school context. Method: This is a qualitative approach, carried out in the municipality of João Pessoa - PB, in two municipal primary schools. The population consisted of 23 participants. The sample consisted of 18 elementary school teachers I, who met the inclusion criteria. The collection met the ethical principles of Resolution 466/2012, was held in December 2018, through the application of a semi-structured script. The empirical data were arranged in two ways, through thematic categories and Word Clouds generated through IRaMuTeQ software. The analysis took place through the content analysis of the thematic modality of Bardin. This study was submitted to the Ethics and Research Committee, protocol 2.983.380 / CAEE 95992318.6.0000.5188. Results / discussion: 2 themes were created and generated 7 which were organized as follows: Child transgeneracy from the point of view of elementary school teachers: Category 1 - Does child transgeneration exist? Category 2 - The construction of identity and gender roles in childhood. Approach in school: importance of dialogue: Category 3 - The experience of trans children in the school context; Category 4 - Trans children: how to cope ?; Category 5 - Discuss the differences in the classroom: is it the way ?; Category 6 - Approach to transgeneracy in school; and Category 7 - The importance of the dialogue between parents and children. Final considerations: it is expected the inclusion of school children transgender, for this, it is necessary to create effective strategies aimed at raising awareness and training of professionals who make up the school environment, especially the teachers in the initial grades.